1967
DOI: 10.1063/1.1710205
|View full text |Cite
|
Sign up to set email alerts
|

Formulas for Phase Velocity and Damping of Longitudinal Waves in Thick-Walled Viscoelastic Tubes

Abstract: The frequency equation for longitudinal waves in a viscoelastic tube of infinite length filled with a viscous fluid is solved for the complex wavenumber, k(=k1+ik2). Thus for two modes, Young's mode and Lamb's mode, an explicit expression for k is obtained which yields the phase velocity c(=ω/k1, ω=radial frequency) and the damping constant k2. The formulas for k, c, and k2 are valid for wall thicknesses up to the size of the inner radius of the tube. The approximation as compared with results obtained numeric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1974
1974
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…A Young wave is generated by an oscillatory pressure forcing in the fluid, while a Lamb wave can be expected when the tube wall is excited harmonically in the direction of the axis. 3 Most of our discussions below will be on the Young wave mode, which is more important in the present study.…”
Section: ͑75͒mentioning
confidence: 99%
See 2 more Smart Citations
“…A Young wave is generated by an oscillatory pressure forcing in the fluid, while a Lamb wave can be expected when the tube wall is excited harmonically in the direction of the axis. 3 Most of our discussions below will be on the Young wave mode, which is more important in the present study.…”
Section: ͑75͒mentioning
confidence: 99%
“…For blood flow in large arteries 3,4 or gas flow in the upper airways, 5 a tube of lumen radius of O͑1͒ cm and longitudinal length of O͑10͒ cm is normally considered. The ratio of wall thickness to lumen radius is approximately 15% in the case of blood vessels and 5% in the case of pulmonary airways.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The scatter of the results was partly due to the motion of the tube not being purely longitudinal. Klip, van Loon & Klip (1967) found that E,/E, was 'frequency dependent and close to 0.02 '. The difference between Klip's value and those of figure 2 will be shown not to have much effect in the application to a tethered tube but to be significant in the case of an unconstrained tube.…”
Section: The Inclusion Of Wall Viscoelasticitymentioning
confidence: 89%
“…(3) Longitudinal resonance of the hose wall may have a significant influence on the coupling motion of the hose and the fluid; (4) For a finite-length hose, the hose end support conditions exert direct effect on longitudinal vibrations of the hose wall and subsequently wave propagation in the fluid. Some efforts have been contributed to wave propagation characteristics in viscoelastic fluid pipes [3][4][5][6][7][8][9][10][11]. But in view of the four facts mentioned above, they can not satisfy the application of actual hoses with finite length owing to infinite-length assumption and other imperfection in theory and experiment.…”
Section: Introductionmentioning
confidence: 99%